(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Augmented Reality (AR) is developing technology for merging interactive virtual forms and shapes into the real-world environment. The AR products in interiors today require lightning and sometimes, spatial conditions, as well as access to some software and hardware elements, provided either by the viewer, or by the host of the location. The study is following some public interiors of the 21st century and investigates the methods of creating and applying of AR sets in their structures. A systematization of AR versions according to the existing relations to the public interiors is presented. The focus is on the evaluation of the use of AR products in interior design, and on the future evolution. The expected results are in the fields of architecture and interior and furniture design.